Advancements in Cholangioscopy: A Case Report with a New Cholangioscope System and Review of Literature - Lopez, Priscilla; Ramchandani, Mohan; Lakhtakia, Sundeep; Inavolu, Pradev; Reddy, D. Nageshwar (Journal of Digestive Endoscopy, 2024)
The field of cholangioscopy is undergoing rapid evolution, marked by continuous innovation. The advent of SpyGlass cholangioscopy has initiated a new chapter, transforming the practice with advancements that include single-operator procedures and the introduction of disposable cholangioscopes. Despite these strides, significant needs remain, including enhancement of optical imaging, improving maneuverability, and expansion of therapeutic channels. This article delves into the recent progress within cholangioscopy, with a particular focus on the clinical applications of the Leinzett Lan-EP-3516 cholangioscope for the management of portal biliopathy. We present a detailed case study demonstrating how this cutting-edge cholangioscope—distinguished by its various sizing options and compatibility with portable devices for immediate imaging—played an important role in the successful treatment of a distal common biliary duct stricture and choledocholithiasis. The device's cost-effectiveness and superior imaging quality signify a notable advancement in cholangioscopic technology, facilitating enhanced treatment pathways for patients with complex biliary disorders. This case exemplifies the dynamic and expanding utility of cholangioscopy in therapeutic interventions and underscores its escalating significance in clinical settings.
Keywords: portal biliopathy; single-operator cholangioscopy; ERCP; stricture